Inovasi Strategi Pengelolaan Lembaga Pendidikan Sekolah Menengah Kejuruan - Iro Waziroh; Agus Zaenul Fitri; Muharofah Nur Safitri (Kependidikan Islam Fakultas Agama Islam, 2023)
Formal education institutions, especially Vocational High Schools (SMK), are formal education institutions that have a vision and mission that directly prepares human resources who are ready to work. The role of Vocational Schools is emphasized by the Vision of the Ministry of National Education in 2011, namely the realization of International Standard Vocational Schools, producing graduates who have national identity, are able to develop local excellence and compete in the global market. This fosters management innovation in vocational high school educational institutions to achieve the expected goals. This research uses a qualitative method approach through field observations, in-depth interviews and documentation analysis for data validity. This research uses triangulation techniques. The results of this research, Manbaul Ulum Vocational School carried out a series of innovations to meet the needs of the local community by opening new departments that suit current market needs. It is hoped that this research will make a positive contribution to the development of school educational institutions, especially in private institutions under the auspices of Islamic boarding schools.